Questioning Multiculturalism: Indigenous Nations and Canadian Law - Megeney, Krista (Université d'Ottawa / University of Ottawa, 2024)
I evaluate Will Kymlicka’s theory of multiculturalism in Multicultural Citizenship: A Liberal Theory of Minority Rights, and how it accounts for Indigenous nations in Canada. I ask whether any failures of multiculturalism can be attributed to either the normative or descriptive claims of his theory. I find points of failure in both claims, depending on the theme in question. Chapter 1 introduces the project and outlines subsequent chapters. Chapter 2 presents an account of Kymlicka’s multiculturalism (including why I chose Kymlicka’s framework as my focus) and the guiding questions of the thesis. Chapter 3 presents major legislation, policy, and jurisprudence in Canada concerning Indigenous nations and multiculturalism in practice. Chapter 4 examines four major claims or themes found in Chapter 2 against the material in Chapter 3: citizenship in Indigenous nations; the characterization of treaties; exercising group-differentiated rights, and; the Canadian state’s exercise of authority over Indigenous nations.
Keywords: Multiculturalism; Philosophy of Law; Political Philosophy; Will Kymlicka; Indigenous Nations; Indigenous Peoples; National Minority; National Minorities; Group-differentiated Rights; Canadian Multiculturalism; Canadian Law; Multiculturalism in Canada; Canadian Politics; First Nations; Canada; Multicultural Citizenship; Normative Political Philosophy; Descriptive Political Philosophy